Absence of effects on the rat sperm quality after subacute exposure to low doses of fungicide prochloraz - Sanabria, Marciana [UNESP]; Pessin, Alessandra [UNESP]; Zanutto, Mirella Rossitto [UNESP]; Perobelli, Juliana Elaine [UNESP]; Guerra, Marina Trevizan [UNESP]; Banzato, Thais Petrochelli [UNESP]; Borges, Cibele dos Santos [UNESP]; Kempinas, Wilma De Grava [UNESP] (Taylor &francis Inc, 2015)
Prochloraz (PCZ) is a fungicide and androgen-receptor antagonist used worldwide in horticulture and agriculture. Pre- and perinatal exposure to this pesticide during sexual differentiation is deleterious for male offspring. Since data on the effects of PCZ on epididymal functions are scarce, and because sperm maturation occurs in this organ, the present investigation aimed to determine whether low PCZ doses administered to rats during the phase of sperm transit through the epididymis might affect the morphophysiology of this organ and sperm quality. Adult male Wistar rats were assigned to 4 different groups: 0 (control, vehicle) or 10, 15, or 30 mg/kg bw/d PCZ diluted in corn oil administered orally for 4 consecutive days. Morphofunctional parameters of the male reproductive tract, hormone concentrations, sperm evaluations, and fertility and histopathologic analysis of testis and epididymis were assessed. There were no statistically significant differences between treated and control groups in relation to all evaluated parameters. Data demonstrated show that PCZ exposure for a brief 4-d exposure and low doses did not produce reproductive toxicity or compromise sperm quality in adult rats.